Prioritizing challenges of agile process in distributed software development environment using analytic hierarchy process. Issue 11 (16th July 2018) - Shameem, Mohammad; Kumar, Rakesh Ranjan; Kumar, Chiranjeev; Chandra, Bibhas; Khan, Arif Ali
Abstract: Software organizations are increasingly combining agile methodologies and distributed software development (DSD) for efficiently and effectively built software products. There are numerous challenges associated with scaling agile methods in a distributed environment. Our study is intended to explore and prioritize the challenges for scaling agile practices in the DSD environment. This study was divided into 3 stages. In the first stage, 22 challenges were identified from literature review and grouped into 4 categories: management, team, technology, and process based on discussion with experts. In the second stage, an online questionnaire study was conducted to validate the identified challenges. Finally, analytic hierarchy process method was used to prioritize challenges and their categories based on their relative importance. The results highlighted that management is a most significant category as compared with the other categories. Similarly, lack of management commitments, lack of effective communication, lack of knowledge sharing, etc are identified as the most significant challenges that need to be focused by the organizations for scaling agile methodologies. On the basis of the research findings, we could conclude that the identified challenges along with their categories provide a robust framework to scale agile methodologies in the DSD environment. Abstract : Investigating the challenges that negatively affect scaling of agile methodologies in the DSD environment, validating the challenges using online questionnaire survey, and prioritizing the challenges using AHP method based on their relative importance, this study provides a robust framework to scale agile methodologies in the DSD environment.